2014
DOI: 10.1080/11250003.2014.912681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of urohyal bone morphology among gerreid fish (Perciformes: Gerreidae)

Abstract: The urohyal bone, located in the central part of the mandibular skeleton, plays an important role in the mouth openingclosing mechanism of fish, and is considered a synapomorphy in teleostean fish. Morphology of the urohyal bone in six species of Gerreidae (Diapterus brevirostris, D. auratus, Eugerres lineatus, E. plumieri, Eucinostomus entomelas and Gerres cinereus) from the Pacific and Atlantic coasts of México was compared, using size and shape measurements. The main goal of the study was to explore the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
1
20
0
3
Order By: Relevance
“…Reproductive isolation between G. cinereus and G. simillimus has resulted in morphological variation that can be quantified by analysing the shape of the bodies, urohyal bones or sagittae otoliths, which are important for taxonomic purposes (Arratia & Schultze, ; Baremore & Bethea, ; Chollet‐Villalpando et al, ; De La Cruz‐Agüero et al, ; Jawad, Khahe‐Jahromi, Teimori, Mehraban, & Esmaeili, ; Nolf, ; Reichenbacher, Sienknecht, Kuchenhoff, & Fenske, ). The discriminant power of body shape was higher than otolith and urohyal shape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproductive isolation between G. cinereus and G. simillimus has resulted in morphological variation that can be quantified by analysing the shape of the bodies, urohyal bones or sagittae otoliths, which are important for taxonomic purposes (Arratia & Schultze, ; Baremore & Bethea, ; Chollet‐Villalpando et al, ; De La Cruz‐Agüero et al, ; Jawad, Khahe‐Jahromi, Teimori, Mehraban, & Esmaeili, ; Nolf, ; Reichenbacher, Sienknecht, Kuchenhoff, & Fenske, ). The discriminant power of body shape was higher than otolith and urohyal shape.…”
Section: Discussionmentioning
confidence: 99%
“…Between 45 and 48 mojarras, according to the structure analysed (Table ), were used for geometric morphometric analyses. Each fish was photographed on its left side, and the otoliths and urohyal bones were removed following the procedures described in De La Cruz‐Agüero et al () and Chollet‐Villalpando et al (), respectively. Fish were photographed with an Olympus SP 320 digital camera fitted with a 3× optical zoom and an Olympus SZ2‐LGBST light source mounted on a base that included a metric scale.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As marine carnivorous species, Gerreidae fishes mainly inhabit tropical and subtropical coastal waters that are frequently affected by freshwater [14,15]. Gerreidae fishes not only play important roles in the domain of marine commercial fishes, but also have become one of the most representative groups in the tropical and subtropical aquatic ecosystems [16]. The data displayed by Fisheries and Aquaculture Department of Food and Agriculture Organization (FAO) have showed that annual capture production of the Gerreidae family has increased from 242 t in 1950 to 12,674 t in 2017, and the genus of Gerres is the domination of the fishery capture with higher exploitation [17].…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role not only in mouth opening-closing mechanism but also in the trophic strategies of fishes (Arratia, G., Schultze, 1990;Chollet-Villalpando et al, 2014b). Considering its function, the urohyal bone can be used in feeding studies to quan-tify the food consumed by piscivorous fish and also other aquatic animals (Johal et al, 2000;Tombari et al, 2010;Perez-Comesaña et al, 2013).…”
Section: Discussionmentioning
confidence: 99%